Cognitive Impairment and Dementia in Parkinson’s Disease: Clinical Features, Diagnosis, and Management - Meireles, Joana; Massano, João (Frontiers in Neurology, 2012)
Parkinson’s disease (PD) is a common, disabling, neurodegenerative disorder. In addition to classical motor symptoms, nonmotor features are now widely accepted as part of the clinical picture, and cognitive decline is a very important aspect of the disease, as it brings an additional significant burden for the patient and caregivers. The diagnosis of cognitive decline in PD, namely mild cognitive impairment and dementia, can be extremely challenging, remaining largely based on clinical and cognitive assessments. Diagnostic criteria and methods for PD dementia and mild cognitive impairment have been recently issued by expert work groups. This manuscript has synthesized relevant data in order to obtain a pragmatic and updated review regarding cognitive decline in PD, from milder stages to dementia. This text will summarize clinical features, diagnostic methodology, and therapeutic issues of clinical decline in Parkinson’s disease. Relevant clinical genetic issues, including recent advances, will also be approached.